Lgr5+ stem cells are indispensable for radiation-induced intestinal regeneration - Metcalfe, Ciara; Kljavin, Noelyn M; Ybarra, Ryan; de Sauvage, Frederic J (Cell stem cell, 2014)
The intestinal epithelium continually self-renews and can rapidly regenerate after damage. Lgr5 marks mitotically active intestinal stem cells (ISCs). Importantly, intestinal homeostasis can be maintained after depletion of Lgr5(+) cells due to the activation of Lgr5(-) reserve ISCs. The Lgr5(-) ISC populations are thought to play a similar role during intestinal regeneration following radiation-induced damage. We tested this regeneration hypothesis by combining depletion of Lgr5(+) ISCs with radiation exposure. In contrast to the negligible effect of Lgr5(+) ISC loss during homeostasis, depletion of Lgr5(+) cells during radiation-induced damage and subsequent repair caused catastrophic crypt loss and deterioration of crypt-villus architecture. Interestingly though, we found that crypts deficient for Lgr5(+) cells are competent to undergo hyperplasia upon loss of Apc. These data argue that Lgr5(-) reserve stem cells are radiosensitive and that Lgr5(+) cells are crucial for robust intestinal regeneration following radiation exposure but are dispensable for premalignant hyperproliferation.